Influence of age on resection of colorectal liver metastases - Schmidt, Thomas; Strowitzki, Moritz; Reißfelder, Christoph; Rahbari, Nuh Nabi; Nienhüser, Henrik; Bruckner, Thomas; Rahäuser, Christoph; Keppler, Ulrich; Schneider, Martin; Büchler, Markus W.; Ulrich, Alexis (Journal of surgical oncology, 2015)
Background and Objectives Only limited data exist investigating the outcome of patients older than 75 years after resection of colorectal liver metastases (CLM). Therefore, the present study aims to evaluate clinical and oncological outcome of elderly patients. Methods A cohort of 405 patients was divided into three age-groups: (1) <65 years; (2) 65-75 years; and (3) >75 years of age. Patients' data were prospectively collected and retrospectively analyzed. We performed survival analysis and added age-correction. Univariate and multivariate analysis was performed to determine independent prognostic risk factors. Results The 5-year survival rate of the >75 years age-group was distinctly decreased, compared to the other age-groups. After age-correction, the 5-year survival rates and the survival curves increased to the greatest extent in patients older than 75 years. The MSKCC score proved to be a sufficient independent prognostic factor in the total patient cohort, patients <65 years and patients 65-75 years. In patients older than 75 years, only localization of the primary tumors was a significant prognostic factor for overall survival. Conclusions Patients' age is no reason to deny surgical treatment of CLM. Prognostic factors, such as MSKCC score, are not sufficient predictors of survival in patients older than 75 years. J. Surg. Oncol. 2015 111:729-739. © 2015 Wiley Periodicals, Inc.
Gesehen am 06.07.2020